THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND COMMITMENT ON JOB SATISFACTION WITH THE WORK ENVIRONMENT AS MODERATING VARIABLES - Rena Augia Putrie; Jenita Jenita; Budi Sulistiyo Nugroho; Lexi Jalu Aji; Arifuddin Arifuddin (ITB AAS Indonesia Surakarta, 2024)
Abstract Job satisfaction has an important role in the company. If employees feel satisfied then all aspects of the company's targets can develop and can easily be achieved. There are several factors that can influence Employee Job Satisfaction, including the Transformational Leadership aspect which is an external aspect and the Employee Commitment aspect which is an internal aspect. This research aims to analyze the influence of Transformational Leadership and Commitment on Employee Job Satisfaction. Different from previous studies, this research adds work environment variables which researchers believe can strengthen the relationship between Transformational Leadership and Commitment to Employee Job Satisfaction. This research is a quantitative research with an exploratory approach. The research results show that each variable of Transformational Leadership and Commitment has a positive and significant effect on Job Satisfaction. Running side by side with the researchers' assumptions, the Work Environment variable can moderate the influence of each of the Transformational Leadership and Commitment variables on Job Satisfaction. Keywords : Commitment, Transforational Leadership, Job Satisfication, Work Environment.